A highly sensitive capillary electrophoresis immunoassay strategy based on dual‐labeled gold nanoparticles enhancing chemiluminescence for the detection of prostate‐specific antigen. Issue 13 (15th May 2017) - Li, Shuting; Shi, Min; Zhao, Jingjin; Zhang, Liangliang; Huang, Yong; Zhao, Shulin
Abstract : An enzyme and antibody dual labeled gold nanoparticles enhancing chemiluminescence strategy was developed for highly sensitive CE immunoassay (IA) of prostate‐specific antigen (PSA). In this work, gold nanoparticles were labeled with horseradish peroxidase and antiprostate specific antigen‐antibody, and used as the marker (Ab * ). After PSA (antigen, Ag) was added into the system, a noncompetitive immune reaction was happen between Ab * and Ag to form an immune complex (Ag–Ab * ). Subsequently, the obtained Ag–Ab * and unreacted Ab * were separated by CE, and the chemiluminescence intensity of Ag‐Ab * was used to estimate PSA concentration. The calibration curve showed a good linearity in the range of 0.25–10 ng/mL. Based on a S/N of 3, the detection limit for PAS was estimated to be 0.092 ng/mL. Proposed CE method was applied for PSA quantification in human serum samples from healthy volunteers and patients with prostate cancer. The obtained results demonstrated that the proposed CE method may serve as an alternative tool for clinical analysis of PSA.